Net survival of women diagnosed with breast tumours: a population-based study in Switzerland - Nena Karavasiloglou; Eleftheria Michalopoulou; Manuela Limam; Dimitri Korol; Miriam Wanner; Sabine Rohrmann (Swiss Medical Weekly)
AIMS OF THE STUDY: Although the incidence of breast carcinoma in situ has been increasing, the prognosis of breast carcinoma in situ patients has not been extensively investigated. Thus, we aimed to compare the characteristics of invasive breast tumours based on whether or not they were preceded by a breast carcinoma in situ and to estimate the 5-year net survival of patients diagnosed with different breast tumours.